Response Surface Methodology For Optimization Of Sodium Sulphate And Sodium Lauryl Sulphate Removal Using Hydroxyapatite Adsorbent - Muhamad, Mimi Suliza; Johar, Muhamad Ridzuan; Sunar, Norshuhaila Mohamed; Ali, Roslinda; Hamidon, Nuramidah; Abdul Hamid, Nor Hazren; Harun, Hasnida (Progress in Engineering Application and Technology, 2020)
Sodium sulphate and sodium lauryl sulphate is contaminant that can be found in surface water resulting from agriculture, industrial, or domestic waste discharge. Sulphate can cause acidic condition to soils and form acid rain that damage plants and buildings. It can also cause laxative effect on humans and livestock. This study is conducted to optimize sulphate removal by hydroxyapatite adsorbent through the application of response surface methodology (RSM). The rate of adsorption on sulphate removal was mathematically describe as a function of experimental parameters and was modelled through RSM via historical data design. The results show that that the response of removal was significantly affected by quadratic term of pH and contact time. The statistical analysis was performed by ANOVA which indicated good correlation of experimental parameters with R2 of 0.98. The optimum operation condition for sodium sulphate was obtain at 26.83 min and pH 7.12, while for sodium lauryl sulphate was at 26.41 min and pH 7.18. The predicted removal was found to be relatively close to experimental removal for sodium sulphate were 60% and 59%, while for sodium lauryl sulphate were 70% and 69%, respectively.